The effect of accounting conservatism, capital intensity and leverage on tax avoidance - Ghina Kemala Dewi; Dini Andriyani (Jurnal Mantik, 2023)
Taxes are a very important source of state revenue besides revenue from natural resources and income from other non-tax sectors. However, the revenue received from the tax sector is not in accordance with what is desired by the state. This happens because there are still interests that encourage individual and corporate taxpayers to minimize their taxes by means of tax avoidance. This study aims to determine and analyze the effect of accounting conservatism, capital intensity and leverage on tax avoidance in food and beverage sub-sector companies listed on the IDX for the 2019-2021 period. The independent variables used in this study are accounting conservatism, capital intensity and leverage, while Tax Avoidance is the dependent variable. The sample used in this study was obtained using a purposive sampling method, so that a total of 12 companies were obtained as a sample of 39 companies as a population with 36 observational data for 3 years. The analysis technique used in this study is multiple linear regression analysis and hypothesis testing using SPSS 25 software. The results of this study indicate that the accounting conservatism variable partially influences tax avoidance, this results from a coefficient value of 6.965 and a significance value of 0.017 <0.05, causing H1 to be accepted. The capital intensity variable partially influences tax avoidance, this results from a coefficient value of 1.363 and a significance value of 0.011 <0.05, causing H2 to be accepted. Meanwhile, the leverage variable partially has no effect on tax avoidance, this is also obtained from a coefficient value of -0.061 and a significance value of 0.721 > 0.05, causing H3 to be rejected. Meanwhile, the simultaneous results of accounting conservatism, capital intensity and leverage affect tax avoidance.